An analysis of variations in morphological characteristics, essential oil content, and genetic sequencing among and within major Iranian Juniper (Juniperus spp.) populations. (June 2021) - Ghorbanzadeh, Amir; Ghasemnezhad, Azim; Sarmast, Mostafa Khoshhal; Ebrahimi, Samad Nejad
Abstract: Junipers ( Juniperus spp.) are important pharmaceutical plants, and they are commonly grown in the northern hemisphere because of the various medicinal properties attributed to the Juniperus genus. However, despite their pharmaceutical and also industrial importance, and despite plant diversity being a common topic of research among professional breeding programs, there is a relatively small body of work which focuses on diversity in juniper, and this is especially true of juniper species that are native to Iran. Thus, the present study set out to investigate juniper diversity via identifying any morphological, phytochemical, and genetic differences among and within three important species of Iranian junipers. The data revealed the terpenoid profiles of the investigated species to be distinct from one another, with α -pinene, β -pinene, myrcene, sabinene, and limonene being the predominant terpenoids detected. Intriguingly, high levels of myrtenyl acetate were detected in the J. sabina tissue collected from the Ramsar site, and this terpenoid was not found in either of the other studied species, nor has it been noted in any other studies that focus on juniper. The genetic variation of Juniperus was analyzed using five ISSR markers and the molecular variance was computed using the GenAlEx software. The results revealed there to be a high degree of genetic diversity both among and within the studied populations. A dendrogram of the genetic data using the UPGMA method with the Dice coefficient divided the genotypes into two main groups. J. communis and J. excelsa were grouped together, while J. sabina was separated into its own group. In general, morphologically speaking, the leaf and cone types were found to be chiefly influential vis-à-vis separating the populations into their respective groups. Ultimately, it is our hope that the biochemical, genetic, and morphological diversity data collected from these species will contribute to the success of future juniper breeding and restoration programs. Graphical abstract: Image 1 Highlights: Morphological variations in cone and leaf size influenced species classification. Terpenoid profiles of investigated species were distinct among species and habitats. Terpenoids like α -pinene, β -pinene, myrcene, sabinene, and limonene were prevalent. High levels of myrtenyl-acetate were detected in the J. sabina sample from Ramsar. Sequencing results revealed high levels of variation among and within the species.